Agonal Factors Distort Gene-Expression Patterns in Human Postmortem Brains - Dai, Jiacheng; Chen, Yu; Dai, Rujia; Jiang, Yi; Tian, Jianghua; Liu, Sihan; Xu, Meng; Li, Miao; Zhou, Jiaqi; Liu, Chunyu; Chen, Chao (Frontiers in Neuroscience, 2021)
Agonal factors, the conditions that occur just prior to death, can impact the molecular quality of postmortem brains, influencing gene expression results. Our study used gene expression data of 262 samples from ROSMAP with the detailed terminal state recorded for each donor, such as fever, infection, and unconsciousness. Fever and infection were the primary contributors to brain gene expression changes, brain cell-type-specific gene expression, and cell proportion changes. Furthermore, we also found that previous studies of gene expression in postmortem brains were confounded by agonal factors. Therefore, correction for agonal factors through probabilistic estimation of expression residuals (PEER) or surrogate variable analysis (SVA) is recommended to control for unknown agonal factors. Our analyses revealed fever and infection contributing to gene expression changes in postmortem brains and emphasized the necessity of study designs that document and account for agonal factors.